2021
DOI: 10.1002/cssc.202100874
|View full text |Cite
|
Sign up to set email alerts
|

Current Developments in the Chemical Upcycling of Waste Plastics Using Alternative Energy Sources

Abstract: The management of plastics waste is one of the most urgent and significant global problems now. Historically, waste plastics have been predominantly discarded, mechanically recycled, or incinerated for energy production. However, these approaches typically relied on thermal processes like conventional pyrolysis, which are energy-intensive and unsustainable. In this Minireview, some of the latest advances and future trends in the chemical upcycling of waste plastics by photocatalytic, electro-lytic, and microwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 90 publications
0
44
0
Order By: Relevance
“…Since the existing artificial photosynthetic systems such as water splitting involve both water oxidation and reduction processes for H2 production, this oxidative solid waste upcycling via LMCT chemistry demonstrated by the Soo group can potentially serve as an alternative to the conventional water oxidation process to generate more valuable products, such as fuels and fine chemicals, in comparison to the O2 from water oxidation. [51][52][53][54][55] Besides well-defined V V complexes with redox non-innocent ligands, the Wang group has shown that commercially available V complexes with simpler ligands such as VO(acac)2 (acac = This is the author's peer reviewed, accepted manuscript. However, the online version of record will be different from this version once it has been copyedited and typeset.…”
Section: Please Cite This Article Asmentioning
confidence: 99%
“…Since the existing artificial photosynthetic systems such as water splitting involve both water oxidation and reduction processes for H2 production, this oxidative solid waste upcycling via LMCT chemistry demonstrated by the Soo group can potentially serve as an alternative to the conventional water oxidation process to generate more valuable products, such as fuels and fine chemicals, in comparison to the O2 from water oxidation. [51][52][53][54][55] Besides well-defined V V complexes with redox non-innocent ligands, the Wang group has shown that commercially available V complexes with simpler ligands such as VO(acac)2 (acac = This is the author's peer reviewed, accepted manuscript. However, the online version of record will be different from this version once it has been copyedited and typeset.…”
Section: Please Cite This Article Asmentioning
confidence: 99%
“…[451] The use of renewable energy in photocatalytic, electrolytic, and microwave-assisted molecular recycling is still at an early bench-scale stage. [506,507] Weckhuysen and coworkers evaluated the available mechanical and molecular recycling processes with respect to their technological and commercial status, end-of-life options for a variety of plastics, and LCA. [80] In terms of CO 2 emission as measured by the CO 2 -equivalent emission index, they arrived at the following ranking: incineration >> landfill, pyrolysis, mechanical recycling > solvolysis, dissolution/precipitation.…”
Section: Gasification Liquefaction and (Hydro)pyrolysismentioning
confidence: 99%
“…[ 451 ] The use of renewable energy in photocatalytic, electrolytic, and microwave‐assisted molecular recycling is still at an early bench‐scale stage. [ 506,507 ]…”
Section: Molecular Recyclingmentioning
confidence: 99%
“…So far, there has been rapid progress in the catalytic upcycling of plastic waste, and several elegant Reviews summarized the development of novel catalytic systems and use of non-conventional energy sources (e. g., solar, electricity, and plasma). [1,[26][27][28][29][30][31][32] However, few are focused on heterogeneous catalysis, which has great potential to make the upcycling process economically feasible and profitable due to its advantage in facile product separation and catalyst recycling.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, carbon materials (e. g., carbon nanotubes, carbon nanofibers, and graphene), hydrogen, and other value‐added chemicals and materials can also be produced through activation of specific bonds such as C−H or C−C bonds in plastic. So far, there has been rapid progress in the catalytic upcycling of plastic waste, and several elegant Reviews summarized the development of novel catalytic systems and use of non‐conventional energy sources (e. g., solar, electricity, and plasma) [1,26–32] . However, few are focused on heterogeneous catalysis, which has great potential to make the upcycling process economically feasible and profitable due to its advantage in facile product separation and catalyst recycling.…”
Section: Introductionmentioning
confidence: 99%